A Concise Total Synthesis of (±)-Mesembrine - Kim, Hyoungsu; Choi, Hosam; Lee, Kiyoun (Synlett, 2018)
A concise total synthesis of (±)-mesembrine has been successfully accomplished in seven steps and 24% overall yield from commercially available 3-ethoxy-2-cyclohexen-1-one. Central to the assembly of the skeleton of mesembrine are a Johnson-Claisen rearrangement for the formation of the benzylic quaternary stereocenter and direct allylic oxidation to generate the substrate for the amidation/transannular aza-conjugate addition reaction.
Keywords: 3a-(aryl)octahydro-indole; allylic transfer; benzylic quaternary stereogenic center; mesembrine; natural products; total synthesis